Regulating mitochondrial oxidative phosphorylation and MAPK signaling: wedelolactone as a novel therapeutic for radiation-induced thrombocytopenia - Li, Zhichao; Li, Qinyao; Wu, Shuang; Mei, Xinyue; Qi, Xiao; Liu, Sheng; Qiao, Gan; Shen, Hongping; Luo, Jiesi; Zeng, Jing; Huang, Feihong; Li, Rong; et al. (Frontiers in Pharmacology, 2025)
IntroductionRadiation-induced thrombocytopenia (RIT) is a serious complication of cancer radiotherapy, for which therapeutic options are limited. This study investigates wedelolactone (WED), a metabolite of a botanical drug, as a potential treatment for RIT.MethodsIn vitro experiments were conducted using Meg‐01 and K562 cell lines to evaluate the effects of WED on megakaryocyte differentiation and maturation. Flow cytometry and phalloidin staining were employed to assess the expression of megakaryocyte‐specific markers CD41 and CD61, as well as nuclear polyploidization. A mouse model of RIT was established to assess the efficacy of WED in restoring platelet counts and regulating hematopoiesis. RNA sequencing and western blot analyses were performed to explore the underlying molecular mechanisms.ResultsIn vitro experiments revealed that WED enhanced megakaryocyte differentiation in a dose‐dependent manner, increasing the expression of lineage‐specific markers CD41 and CD61, and promoting polyploidization and cytoskeletal reorganization. In vivo, WED significantly restored platelet counts in the mouse model of RIT and promoted the production of hematopoietic stem cells (HSCs), megakaryocytes, and reticulated platelets. RNA sequencing and western blot revealed that WED-induced megakaryocyte differentiation involves the regulation of mitochondrial oxidative phosphorylation mediated by the AMPK signaling pathway and activation of the MAPK signaling pathway. Inhibition of mitochondrial oxidative phosphorylation or MAPK signaling suppressed WED‐induced megakaryocyte differentiation, highlighting the central role of these pathways.DiscussionThese findings indicate that WED could be a promising therapeutic candidate for RIT, acting through the modulation of oxidative phosphorylation and MAPK signaling pathways to enhance thrombopoiesis.